The Influence Of Co2+ Concentration On The Electrodeposition Of Znni Films To Obtain The Znni–co Composite Coatings - Diafi, M.; Degheche, K.; Ben Temam, H. (University of Eloued جامعة الوادي, 2017)
In this work we have done an experimental study of Zinc- Nickel composite coatings. For this, the influence of the cobalt concentration was the principal object in order to improve the resistance of the corrosion of the coatings, which has been made by electroplating on steel substrates previously treated, have been studied by several characterization methods, as the X-ray diffraction, micro-hardness measurement and scanning electron microscopy (SEM), protection against corrosion properties studied by potentiodynamic polarization measurements (Tafel) and electrochemical impedance spectroscopy (EIS) to the potential of corrosion free . The parameters wich characterize the corrosion behavior; can be determined from the Nyquist plots. It has been observed that the ternary Zn–Ni–Co alloy is characterized by enhanced the resistance of corrosion compared to the binary Zn–Ni alloys. and the addition of Co in the Zn-Ni increases the micro-hardness, XRD and SEM results and identify any coatings Zn-Ni-Co alloy composition reveals that γ-Ni5Zn21 phase, Co matrix phase and pure zinc phase.
Articale in Journal of fundamental and Applied Sciences Vol. 09, N. 01
Keywords: Alloy, Nickel, Zinc, Microhardness, Electrodeposition, Corrosion resistance.